Relationship between upper limb motor function and activities of daily living after removing the influence of lower limb motor function in subacute patients with stroke: A cross-sectional study - Haruka Yamamoto; Kazuya Takeda; Soichiro Koyama; Keisuke Morishima; Yuichi Hirakawa; Ikuo Motoya; Hiroaki Sakurai; Yoshikiyo Kanada; Nobutoshi Kawamura; Mami Kawamura; Shigeo Tanabe (SAGE Publishing, 2020)
Background Previous studies have reported a relationship between upper limb motor function and activities of daily living. However, their relationship after removing the influence of lower limb motor function has not been clarified. Objective This study aimed to investigate the relationship between Fugl-Meyer assessment upper limb and total Functional Independence Measure motor score and between Fugl-Meyer assessment upper limb and each item contained in Functional Independence Measure motor score after eliminating the influence of the motor function of the affected lower limb. Methods This retrospective cross-sectional study included 58 subacute stroke patients. To investigate the relationship between the Fugl-Meyer assessment upper limb and total Functional Independence Measure motor score before and after removing the influence of Fugl-Meyer assessment lower limb, Spearman's rank correlation coefficient and partial correlation analysis were used. Additionally, the relationship between Fugl-Meyer assessment upper limb and each item of Functional Independence Measure motor score after removing the influence was assessed. Results Before removing the influence of Fugl-Meyer assessment lower limb, Fugl-Meyer assessment upper limb was strongly correlated with total Functional Independence Measure motor score (r = 0.74, p < 0.001). However, it became weak after removing the influence (r = 0.27, p = 0.04). Regarding each item of Functional Independence Measure motor score, Fugl-Meyer assessment upper limb was correlated with grooming (r = 0.27, p = 0.04), bathing (r = 0.28, p = 0.03), dressing upper body (r = 0.33, p = 0.01), dressing lower body (r = 0.31, p = 0.02), and stair-climbing (r = 0.31, p = 0.02) after removing the influence. Conclusion These findings suggest that the relationship between the upper limb motor function and activities of daily living is strongly influenced by lower limb motor function.